A work study on Jemma, Inc. - Mueco, Francis Lee (College of Engineering, 1997)
Jemma Inc. is a publishing company which was established in 1998 by Mr. Joel Dayao. It was named after his wife, Mrs. Jemma Dayao. It reprints and distributes a wide range of books after having granted the copyrights. The group members conducted several plant visits to be able to familiarize themselves with the production system and accurately document each of the processes. No historical data were available. Data gathering was done through actual interviews with workers and by more observation. The manufacturing of a book, basically, consists of eight processes: text-shooting and processing, stripping, plate-making, printing, folding, gathering, binding and cutting. All these processes are done in the plant, except for binding. After data gathering, the group constructed a Process Failure Mode and Effects Analysis (FMEA) to identify the critical processes or those processes which produce a considerable number of defectives. A pareto diagram of the processes and their corresponding defective rates was also presented to supplement the FMEA. Analyses of data and of said statistical tools showed that printing produces the most number of rejects. It exceeds the 10% allowance allotted by the company for rejects having a defective rate of 10.75%. This establishes that the production system has indeed, a problem. An Ishikawa diagram on printing defectives was done to identify probable causes of such a high defective rate on printing. Analysis of the diagram showed that printing rejects mostly result from human error and lax inspection. Inspection is the main quality activity in the plant. Workers and machine operators perform inspection before and after their respective processes. However, strict inspection is only done in the first three processes, which are text-shooting and processing, stripping and plate-making, because defects not detected at these stages will be carried on to the succeeding stages. Lax inspection happens in other processes, which is one reason why printing produces a big number of defectives. In order to remedy the printing problem, the group recommended that random sampling be performed in printing. A sampling plan was designed which would require the operator to randomly get 50 samples from a lot size of of 5,000, and reject the lot if it has 10 or more defectives. A rejected lot will have to undergo 100% inspection. The group also designed a Production Data Form to aid the company in monitoring costs. IT lists the projected quantity of raw materials to be used against the actual quantity used, as well as, types of rejects in every process and their corresponding frequencies of occurrence. with this knowledge, management will know where to focus their attention and do some investigation.